Mana Moana: Understanding the Place of Moana in Aotearoa’s Architecture - Tone, Lama; ‘Ilaiū Talei, Charmaine (Art/Research International)

(untitled) (University of Alberta, 2024)
Our article is an investigation of the architectural meanings of Moana when located in Aotearoa, as Pacific practitioners, designers, and academics. This article will traverse sensitive topics, such as how Aotearoa’s Pacific peoples relate to Tangata Whenua today and how this is expressed in the built space. How can we navigate Te Tiriti o Waitangi through our voyaging histories, moving beyond the muddy relations within urban conditions in Aotearoa? The phrase Mana Moana is used to refer to the ancestral relationships between Tangata Whenua and the wider Moana, or vast Pacific region, as a positioning framework for our discussions. Mana Moana reinforces connected genealogies of Māori and Pacific peoples across deep time and space beyond the shores of Aotearoa, New Zealand. The article draws on architectural case studies from Aotearoa that investigate placemaking concepts and praxes that provoke, educate, and inspire current and future built environments of Aotearoa, New Zealand.